A review on extraction, isolation, characterization of bioactive compounds obtained from agri-food waste and their potential for industrial application - Njewa, Joel B.; Monjerezi, Maurice; Kabanga, Lucia; Kumwenda, Felix; Sumani, Jimmy (Frontiers in Chemistry, 2025)
The increased global food demand has resulted into extensive agricultural activities to offset the demand. The agri-activities generates large volumes of agri-food wastes (AFW) which creates disposal challenges and environmental pollution concerns. However, agri-wastes possess essential bioactive compounds with industrial applications. The primary focus of the study is to discuss techniques used in extraction, isolation, purification and characterisation of bioactive compounds found in AFW and their potential industrial applications. Traditional and emerging extraction processes; solid-liquid phase, liquid-liquid phase, distillation, crystallisation, thin layer chromatography and gel filtration chromatography are used for purification and isolation of bioactive compounds. FT-IR, NMR, UV-Vis and GC-MS analytical techniques are usually used in characterisation of bioactive compounds. AFW are reported to contain high levels of bioactive compounds with excellent antioxidants properties and biological activities that are ideal for cosmetics, pharmaceuticals and nutraceutical industries. However, the scalability of the use of bioactive compounds from AFW in various industries face challenges such as the use of large volumes of solvents and reagents in the extraction process that are a threat to human health and cause environmental pollution. The occurrence of phytochemical compounds with different properties and characteristics presents difficulty during extraction and purification processes. It is suggested that the use of pretreatment methods, innovative biological techniques and building closed-up systems that aim to repurpose the AFW into new products can promote their scalability and reduce environmental effects.